Recent Experiences and Challenges of Military Physiotherapists Deployed to Afghanistan: A Qualitative Study - Rowe, Peter (University of Toronto Press Incorporated, 2011)
Purpose: Military physiotherapists in the Canadian Forces meet the unique rehabilitation needs of military personnel. Recently, the physiotherapy officer role has evolved in response to the Canadian Forces' involvement in the combat theatre of operations of Afghanistan, and this has created new and unique challenges and demands. The purpose of this study was to describe the experiences and challenges of military physiotherapists deployed to Afghanistan. Methods: A qualitative research design guided by descriptive phenomenology involved recruitment of key informants and in-depth interviews as the data collection method. The interviews were transcribed verbatim and the data analyzed using a foundational thematic analysis approach. Strategies of peer review and member checking were incorporated into the study design. Results: Six military physiotherapists were interviewed. They described rewarding experiences that were stressful yet highly career-satisfying. Main challenges revolved around heavy workloads, an expanded scope of practice as sole-charge practitioners, and the consequences and criticality of their clinical decisions. Conclusions: Our findings suggest that enhanced pre-deployment training and the implementation of a stronger support network will improve the capabilities of military physiotherapists deployed to difficult theatres of operations. This type of systematic and comprehensive research is needed to assist the Canadian Forces in proactively preparing and supporting physiotherapists deployed on future missions.